ANALISIS PENDAPATAN USAHATANI KAKAO DI DESA SIONTAPINA KECAMATAN LASALIMU SELATAN KABUPATEN BUTON - Suriadi Suriadi (Media Agribisnis, 2018)
This research aims to analyze the amount of income earned by farmers from cocoa farming. This research was conducted from May to June 2013 in Siontapina village of Lasalimu Sub-district of Buton Regency. The research sample is determined by sample random techniques (Simple random sampling method) with 30 people. Research data obtained through direct interviews with farmer respondents using a questionnaire. While secondary data is obtained from the village office/administrative and related institutions were analyzed descriptively and quantitatively used to determine the level of income by the formula : N1 = TR- TC, TR = P x Q, TC = TFC + TVC, comparative analysis: Revenue - cost ratio for comparing the difference between the value of production and the cost of production by the formula RC ratio : R/C = Revenue (TR) / Total Cost (TC). The results showed that the income earned by farmers from cocoa farming with land area ranges between 1 to 3 ha of IDR 8,109,000 - 35,437,000/year, with income per capita monthly average IDR 675,750,00 so that Siontapina village had not been considered poor, the average income earned by farmers in cocoa farming with land area- average of 2,05 hectares of IDR 18,426,767/year. Cocoa farming by farmers still does because based on the results of feasibility analysis obtained a value of 5.7. This illustrates that every cost IDR 1.00 incurred by farmers will gain acceptance by IDR 5.7. So, farmers are expected to carry cocoa farming is more responsive and responsive to the presence of new technologies that can increase cocoa production. Keywords: revenue, cost of production, cocoa.